Treatment of severe arterial limb ischemia in patients with multifocal atherosclerosis and chd infusion of 0.01 % nitroglycerin solution - A. N. Shcherbyuk; V. L. Lemenev; B. I. Yaremin; V. M. Manuylov; Ya. E. Nemstsveridze; R. I. Stepanova; L. R. Derbina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Occlusive lesions of the main arteries of the extremities are a common and severe disease that leads to disability and has a high rate of death [1]. Many different drugs are known for the treatment of this pathology, however, despite the large number of pharmacological drugs and conservative treatment methods, surgical methods of treatment are the most effective in terms of saving the limb [3, 4]. However, methods of conservative therapy continue to be the most important component of the treatment of arterial limb ischemia, which requires the development of more effective methods. As a result of the use of intravenous administration of a 0.01 % solution of nitroglycerin for the treatment of arterial ischemia of the extremities in patients with coronary artery disease, it was possible to obtain good immediate results in an average of 57.3 % of cases.